The Archetypal Types based on Jungian’s Psychology in Madura Tales - Diana, Putri Nur; Harits, Imron Wakhid; Chudy, Stefan (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2022)
This paper aims to examine archetypal elements in some Madura Tales from Carl Gustav Jung in Marie Louis Von Franz’s perspectives. This research analyzes Three Madura tales there are Megaremeng and Other Stories (A Selection of Madura Tales) book: The Horse and the Cow, Princess Tajungan, and When the Monkey can Speak. Thus, archetypal elements will be depicted in characters and symbols along with the representative of Madurese cultures and traditions appearing in the stories. This study employs a qualitative method to describe and explain the characters‘ archetypes through their behavior, attitude, and emotion. The results show that In the Horse and the Cow shows (1) the myth of a horse and a cow, (2) the archetype of the Jungle King, and (3) The horse‘s archetype of shadow. Princess Tajungan shows (1) the myth of Tajungan Village, (2) the archetype of Wira as a hero, (3) and the symbol archetype of the rack, rooster, and Pesa’an costume. Whereas When the Monkey can Speak shows (1) the archetype of Kyai Barambang, (2) the archetype of the King's son, and (3) the symbol archetype of the monkey. Furthermore, the children's literature will figure out that this research expects that children will become the next virtuous generation.